Efektivitas Penerapan Pelayanan Program Perizinan Berusaha Berbasis Online Single Submission (OSS) Di Dinas Penanaman Modal Dan Pelayanan Terpadu Satu Pintu (DPMPTSP) Kota Tanjung Pinang - Ewi Suyani; Nafis Laelatullaena (Repeater : Publikasi Teknik Informatika dan Jaringan, 2024)
This study examines the meticulous and thorough execution of the Online Single Submission (OSS) in the Tanjung Pinang City Investment and One Stop Integrated Service Office.The main focus involved the complexity of the community’s lack of deep understanding of the business licensing stages, while also exploring the technical barriers that accompanied the integration of the OSS system. The research objectives included an in-depth evaluation of the programme’s operational success, an analysis of the level of stakeholder satisfaction involving business owners, as well as a detailed investigation into the level of efficiency of the OSS implementation. The research method, applied in a descriptive qualitative approach, involved in-depth interviews, rigorous documentation analysis, and a comprehensive literature review. The findings highlight positive progress, although obstacles remain, both in terms of public understanding and technical constraints in OSS operations. In conclusion, the research provides very specific recommendations, including a careful restructuring of the OSS system, a more focused socialisation strategy and breakthrough interventions to improve the effectiveness of the OSS in the future.